Protein degradation by Lactobacillus plantarum and Lactobacillus casei in a sausage model system - Fadda, Silvina G. (2002)
The proteolytic activity of a starter culture involving Lactobacillus plantarum and Lactobacillus casei towards meat sarcoplasmic and myofibrillar proteins during the fermentation of a sausage-like system was studied. After 96 h of incubation the proteolytic system of L. plantarum CRL681 caused a degradation of both sarcoplasmic and myofibrillar proteins, whereas L. casei CRL705 showed a different affinity to meat proteins. The inoculation of both strains showed a higher activity toward sarcoplasmic fraction. These results correlated with a high rate of sarcoplasmic protein degradation observed in SDS-PAGE analysis. The generation of free amino acids as well as the pH drop at the end of the incubation period was maximal in presence of the mixed starter culture, thereby demonstrating the suitability of these strains to be used in the fermentation of meat products.